Calving distribution of Alaska's Steese-Fortymile caribou herd: A case of infidelity? - Valkenburg, Patrick; Davis, James L. (Rangifer, 1986)
The Steese-Fortymile caribou (Rangifer tarandus granti) herd has changed its calving distribution frequently during the past 30 years. A «traditional» calving area, used for decades, west of the Steese Highway (Preacher Creek) was abandoned after 1963. By the early 1970's, a new calving area had been established 74 km to the southeast in the Birch Creek drainage. This new calving area was abandoned after 1976. From 1977 through 1983, calving occurred in annually variable locations approximately 136 km southeast of the Birch Creek calving area. In 1984, however, the herd again calved in the general vicinity of the Birch Creek calving area. General characteristics of the various calving areas are described, and calving distribution is discussed in relation to herd size, development and disturbance, predator abundance, and other factors. Location of calving in recent years was unpredictable, which warrants reconsidering the merit of protecting only previously important calving grounds.